Ticks are unlikely to play a role in leprosy transmission in the Comoros (East Africa) as they do not harbour M. leprae DNA - Krausser, Lena; Chauvaux, Elien; Van Dyck-Lippens, Magalie; Yssouf, Amina; Assoumani, Younoussa; Tortosa, Pablo; de Jong, Bouke Catherine; Braet, Sofie Marijke (Frontiers in Medicine, 2023)
Leprosy, one of the oldest known human diseases, continues to pose a global challenge for disease control due to an incomplete understanding of its transmission pathways. Ticks have been proposed as a potential contributor in leprosy transmission due to their importance as vectors for other infectious diseases. In 2010, a sampling of ticks residing on cattle was conducted on the islands Grande Comore, Anjouan and Mohéli which constitute the Union of the Comoros where leprosy remains endemic. To investigate the potential role of ticks as a vector in transmission of leprosy disease, molecular analyses were conducted. Out of the 526 ticks analysed, none were found to harbour M. leprae DNA, as determined by a quantitative polymerase chain reaction (qPCR) assay targeting a family of dispersed repeats (RLEP) specific to M. leprae. Therefore, our results suggest that in the Union of the Comoros, ticks are an unlikely vector for M. leprae.